Characterization of chitin from Crassostrea bilineata shells from Iloilo, Philippines - Concio, Reginald G.​; Debuque, Nathalie Ann F.​; Santos, Mikaella B.​
Chitin is a polysaccharide of [β-(1 → 4)-2-acetamido-2-deoxy-D-glucopyranose]ₙ which normally has 1,000-3,000 monomer units. It is regarded as the second most abundant biological material in the world after cellulose. In this study, chitin was extracted from the shells of C. bilineata from Iloilo, philippines using for steps namely, demineralization, deproteinization, decolorization,and elimination of lipids and pigments. The extracted chitin was then subjected to several characterization tests including IR, thermal analysis, particle morphology, moisture content, solubility, swelling capacity, flow properties, and compatibility studies. The IR spectra of the extracted chitin was similar to the chitin reference and to ones in literature. Thermal analysis of the extracted chitin showed an endothermic peak at 322.10℃. Under SEM, the sample was observed to have a equant sphere shape with rough, fibrous, pitted surface. It was also tested to have a swelling capacity of 380% and a moisture content of 2.83%. The extracted chitin was insoluble in both water and ethanol at room temperature. Lastly, the sample was observed to have an excellent powder flow. In conclusion, chitin was successfully extracted with a 2.18% yield. It was also characterized and found to be compatible with magnesium stearate and croscarmellose while incompatible with starch.